Adoption level of improved dairy husbandry practices in tribal areas of Southern Gujarat (Indian Journal of Animal Production and Management, 2024)
The present study was conducted in the Valsad district of Southern Gujarat. Total 240 respondents were interviewed for the questionnaire prepared about improved dairy husbandry practices adopted by them. The findings indicated that majority of dairy farmers had medium adoption level on different component of improved dairy husbandry practices viz. 67.92% for housing, 64.58% for feeding, 63.34% for breeding, 70% for healthcare, 64.58% for milking management and 70% for calf rearing. The overall adoption levels of the respondents in improved dairy husbandry practices fall under low, medium and high categories are 14.58%, 67.08% and 18.33%, respectively. The adoption index of different aspect of improved dairy husbandry practices of housing, feeding, breeding, health care, milking and calf rearing were 44.89, 29.04, 58.04, 43.31, 37.06 and 54.04%, respectively and overall adoption index of improved dairy husbandry practices was 44.4% which indicated low adoption level of dairy farmers in the study area.
Keywords: Adoption; Dairy Husbandry; Practices; Tribal areas